Variation of nucleocapsid protein gene of infectious bronchitis virus and its expression in Escherichia coli - ZHOU Ji-yong; DING Hong-mei; CHENG Li-qin; Jimmy Kwang (浙江大学学报. 农业与生命科学版)
Nucleocapsis (N) protein gene is one of the major structural protein genes of infectious bronchitis virus (IBV). Our previous studies have indicated that IBV strain ZJ971 causes proventriculus lesions while strains N and X result in chicken nephritis. This research was undertaken to investigate their variance where two specific primers were designed and synthesized according to the published sequence of N protein gene of IBV strain Beaudette. cDNAs of N gene were amplified by reverse transcription polymerase chain reaction (RT-PCR) from viral RNAs of IBV-ZJ971, N, X and H52 strains, cloned into vector pBluescript SK (+) and sequenced. Sequencing results showed that complete open reading frame (ORF) of N gene encode a protein of 409 amino acids that was 1230 bp in length from IBV strains ZJ971, N, X and H52. When the nucleotide and predicted amino acid sequence of N gene is compared with that of the known IBV strains in GenBank, the homology of nucleotides range from 87.0% to 98.6%, 86.6% to99.7%, 86.3% to 99.7% and 87.2% to 98.5% for ZJ971, N, X and H52, respectively. Furthermore the similarities of predicted amino acids range from 90.0% to 97.8%, 90.5% to 98.8%, 90.0% to 98.8% and 91% to 98% respectively. Based on the analysis of the predicted amino acid sequence, it was noted that IBV strain ZJ971 was different from the other 11 IBV strains in that mutation occured at sites 111, 117, 142, 171 and 401. Remarkable variation of amino acids, distinct from 10 IBV strains shown, were observed at sites 46, 48, 189, 190, 220, 223, 236, 237, 240, 286, 299, 301 334, 335, 336 and 351. cDNA of N gene for ZJ971 strain was subcloned into prokaryotic expression vector pBV220. Upon expression in Escherichia coli. DH5α, a specific non-fusion protein of 45 kD was detected by western-blotting assays using monoclonal antibody against N protein of IBV. These studies suggested that IBV strains ZJ971, N and X were three novel IBV strains of China origin.